Evaluating the Aptness of Demolished Cement Concrete in a Bituminous Mix for Low-Volume Roads in Bangladesh - Chowdhury, Aditya; Deena, Tasnim Khandaker; Palit, Swapan Kumar (AMC Indian Journal of Civil Engineering, 2024)
The most emerging concern has recently surfaced as handling and storing trash from demolished cement concrete worldwide. In recent years, the use of demolished cement concrete as a construction material has become a worldwide practice. The main purpose of this research is to utilize this demolished cement concrete as a replacement for natural coarse aggregate in the surface layer of flexible pavement construction for low-volume roads. In this study, Optimum Bitumen Content (OBC) has been determined after the evaluation of Bituminous mix prepared with 0%, 20%, 40%, and 60% replacement of natural coarse aggregate with demolished cement concrete. Furthermore, Water Sensitivity tests have been performed to find out the moisture resistance of the Bituminous mix. From the experimental investigation, it has been found that the OBC of the Bituminous mixes for 0%, 20%, 40%, and 60% replacement are 5.35%, 5.83%, 5.75%, and 6.18% respectively. The Marshall properties have been evaluated and it was found that 0% and 20% of replacements fully satisfy the Marshall criteria and 40% of replacements satisfy marginally. Also, the Water Sensitivity test results remain within the specified limit. Moreover, the cost of road construction can be reduced by 9% to 18.5% due to the utilization of cement concrete waste. So, demolished cement concrete can be reused as a replacementÂ for natural coarse aggregate in the Bituminous surface layer of low volume road which leads to a reduction of environmental hazard.